Retrospective study of patients with suspected inborn errors of metabolism at Siriraj Hospital, Bangkok, Thailand (1997-2001) - Pornswan Wasant (2018)
Introduction: This retrospective clinical study was carried out on patients with suspected inborn errors of metabolism (IEM) at Siriraj Hospital during 1997-2001. The authors investigated 114 patients by quantitative plasma amino acid analysis. Objective: The objective of this study was to collect and analyze epidemiologic and specific clinical data of IEM, especially in small-molecule diseases. Material and Method: All patients were categorized into 2 major groups: 1) positive diagnoses for IEM 2) negative diagnoses for IEM. The two groups were investigated, studied including statistical analysis. Results: The authors found that most IEM ascertained through plasma amino acid analysis were small-molecule diseases (74.3%) and amino acid disorders consisted of the most frequent disorders. The presented data demonstrated that the ratio of positive diagnoses to all patients studied was 1:8. Epidemiological data showed there were more male than female patients. Onset of diseases occurred predominantly during the first month of age, and was rarely found after 3 years of age. There were histories of consanguinity in half of the IEM patients. The most common presenting symptom was acute metabolic encephalopathy and specific signs for small-molecule disorders included hepatomegaly, unusual urine odor, acidosis, hyperammonemia, alteration of consciousness, and ketosis/ketonuria. These signs or symptoms indicated further metabolic investigations. Conclusion: Comparison of the data from Thailand with other countries showed both similarities and differences to the Caucasian population. Thus, further studies in IEM are much needed for the Thai population.